Giant negative electrocaloric effect and energy storage response in 0.94(K0.5Na0.5)NbO3-0.06SrMnO3 nanocrystalline ceramics. Issue 17 (1st December 2018) - Kumar, Raju; Khurana, Divyansh; kumar, Ashish; Singh, Satyendra
Abstract: We report the electrocaloric (EC) effect investigation on lead-free 0.94(K0.5 Na0.5 )NbO3 -0.06SrMnO3 nanocrystalline ceramics by an indirect thermodynamic method using Maxwell's relations. The maximum value of the negative EC effect ( Δ T max = − 1.66 K ) was observed at 459 K near the transition temperature at the field of 50 kV/cm. The corresponding EC responsivity was calculated to be − 3.32 × 10 − 7 K m / V under 50 kV/cm at 459 K whereas the coefficient of performance (COP) and recoverable energy density ( W rec ) were found to be 1.03 and 0.17 J / cm 3, respectively under 50 kV/cm at 443 K. The observed values of negative EC effect, and EC responsivity are larger than any other lead-free ferroelectric ceramics with good COP and W rec value. The results are interesting to improve the cooling efficiency and energy storage for device application.